Nouveau-riche nationalism and multiculturalism in Korea : a media narrative análisis - Han, Gil-Soo (Routedge advances in Koren Studies, 2018)
The unprecedented economic success of South Korea since the 1990s has led in turn to a large increase in the number of immigrants and foreign workers in Korean industries. The aim of this book is to describe and explain the experiences of discrimination and racism that foreigners and 'new' Koreans have faced in a multicultural South Korea by looking at how society has treated the foreigners and what their experiences have been given that common discourse about race in Korea surrounds issues of Korean heterogeneity and pure blood nationalism"